Application of Concrete Media to Improve Learners' Knowledge of Plants - Wirawan, Wijanarko Bagus (Universitas Sebelas Maret, 2022)
This research aims to teach 4th grade elementary school students about various aspects of plants, including plant structure, the function of various parts of plants, and the importance of plants in everyday life. The method used is collaborative learning which involves observation, experimentation and discussion. In this research, students are given the opportunity to observe various types of plants, such as flowering plants, non-flowering plants and vines. They also study the basic structures of plants, such as roots, stems, leaves, and flowers. Apart from that, students are taught about the role of plants in maintaining the balance of the ecosystem and the availability of oxygen in the atmosphere. Through discussions and group activities, students also understand the importance of protecting the environment and caring for the plants around them. They learn how to care for ornamental plants and trees at school and at home. The research results show that this learning method is effective in increasing students' understanding of plants and how they play an important role in their lives. It is hoped that this research can make a positive contribution in increasing students' awareness of the importance of protecting nature and plants in the ecosystem. In conclusion, this research helps 4th grade elementary school students to understand various aspects of plants and the importance of plants in everyday life. Learning methods that are active and involve observation and experimentation help students learn better and appreciate the nature around them.